PERANCANGAN DAN IMPLEMENTASI DATA WAREHOUSE SYSTEM DI CV. RIZKY ABADI BERSAMA BANDUNG - Ardelia Astriany (POLITEKNIK PIKSI GANESHA, 2018)
Technology has experienced very rapid development in various disciplines, it will trigger the development of processing data in a database. The presence of data warehouse technology will facilitate access to data quickly. It is useful to obtain information that can support the decision-making process and produce reports in accordance with the perspective desired by the company's management. The implementation of this data warehouse system is expected to make it easier for the Admin to implement Goods Data management in a computerized and effective manner. The design and manufacture of this system uses the SDLC methodology (System Development Life Cycle). The design of the system uses Microsoft Visual Studio Ultimate 2012. Data storage uses the Microsoft Access 2010 database. The results of the research have built a Goods data management system in CV. RizkyAbadiBersama with communicative menus for processing data items, as well as reports.